Analisis konsep Abrahamic Faiths dan kaitannya dengan pluralisme Agama - Suhaida Shaharud-din; Khadijah Mohd Khambali @ Hambali (Universiti Kebangsaan Malaysia, 2012)
Abrahamic Faiths often referred to Judaism, Christianity and Islam that put this categorization based on a number of features common to all three religions in the same cluster. Terminology of Abrahamic Faiths within the contemporary real-world comparative religion has been manipulated by leaders to strengthen the concept of religious pluralism is not only related to the Abrahamic Faiths, but also related to wad'i religions on the basis of prophetic chronology of Abraham. In reality, the position of Abrahamic Faiths has evolved appropriate real philosophical doctrines that every reality is much different. Therefore, this study will reveal and analyze the concept of Abrahamic Faiths in the context of religious studies to provide clarification on the ambiguity arising out of the equation. In addition to analyzing relationship between religious pluralism that makes the concept of Abrahamic Faiths seen as one of the themes of religious generalizations on the basis of prophetic chronology equation as the way for religious tolerance.